Numerical Method for Power Losses Minimization of Vector-Controlled Induction Motor - Alex Borisevich (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
The paper devoted to energy efficiency maximizing problem of the induction motor under part-load conditions. The problem is formulated as the minimization of ohmic losses power as a function from flux-producing current in field-oriented motor operation. Control input precompensation which transforms the dynamic time-varying optimization problem to stationary one is introduced. Adjustment rule for control variable is proposed which speeds-up the method convergence in comparison with linear variation of input. Finally a new continuous-time search algorithm for solving the problem of minimizing power consumption was given. The statements on method behavior were formulated and convergence to local minimum was proved. The method verified in simulation and in hardware experimental setup.